Factors that Motivates Nurses to Transfer to other Fields of Nursing - BONAYON, KIRSTY JOANNE KAE; Alcala, Emerlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
Amid escalating global nursing shortages projected at 13 million by 2030 (ICN, 2022) and Philippine district hospital crises—chronic 1:20+ nurse-to-patient ratios, 80% contractual precarity, burnout cascades—this quantitative descriptive study conducted at Dr. Lorenzo P. Ziga Memorial District Hospital (Tabaco City, Albay) elucidates contributory factors motivating intra-professional transfers among 72 registered nurses via validated 5-point Likert instruments analyzed through weighted means (WMs) and triangulated against Herzberg’s Two-Factor/Maslow Hierarchy frameworks, revealing young (26-30 years: 34.72%), female (75%), contractual (44.44%) early-career (1-3 years: 43.06%) cohort primarily in wards (41.67%) exhibiting Agree-level transfer intents (WM=3.95) driven by hygiene deficits—workload overload (WM=4.20 Strongly Agree), staffing shortages compromising safety (WM=4.05/3.95 Agree), compensation neutrality (WM=3.30)—juxtaposed against motivator strengths in recognition (WM=3.70-3.85 Agree) and professional dignity (WM=3.55-3.85 Agree) yet undermined by emotional exhaustion (WM=4.05 Agree), perceived role stagnation (WM=4.00 Agree), and alternative fields’ superiority (WM=3.65 Agree), corroborating Pepito et al. (2025) RA 9173 implementation gaps, Labrague & de los Santos (2020) burnout predictors, and global precedents (Zheng et al., 2024), ultimately prescribing targeted staffing audits, compensation recalibrations, wellness ecosystems, and career ladders to fortify positional retention stabilizing Bicol Region’s public health continuum.